Organic compound with furan-containing structure as mother nucleus and application of organic compound
By using organic compounds with a parent core with a furan-containing structure as NCGL material, the problems of low electron injection efficiency and short OLED life in stacked OLED are solved, and the effects of reducing driving voltage, improving luminous efficiency and extending life are achieved.
Patent Information
- Application Number
- CN202510199503.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-24
AI Technical Summary
In stacked OLEDs, the energy level difference between NCGL and PCGL leads to low electron injection efficiency, and conventional NCGL doping with alkali metals will lead to a shorter OLED lifetime.
Organic compounds with a parent nucleus containing a furan structure are used as NCGL materials, and charge generation and electron transport performance are enhanced through their suitable LUMO and HOMO energy levels.
It reduces the driving voltage of OLED, improves the luminous efficiency, and extends the life of OLED devices, while improving the film stability and heat resistance of the material.
Smart Images

Figure CN119661560A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor materials and relates to an organic compound whose parent core contains a furan structure and application thereof. Background Art
[0002] Organic light emitting diodes (OLED) device technology can be used to manufacture new display products as well as new lighting products. It is expected to replace existing liquid crystal displays and fluorescent lighting, and has a wide range of applications. OLED light-emitting devices are like sandwich structures, including electrode material films and organic functional materials sandwiched between different electrode film layers. Various functional materials are superimposed on each other according to their uses to form OLED light-emitting devices. As a current device, when voltage is applied to the electrodes at both ends of the OLED light-emitting device and the electric field acts on the positive and negative charges in the organic layer functional material film layer, the positive and negative charges are further compounded in the light-emitting layer, generating OLED electroluminescence.
[0003] In a stacked OLED, two or more independent light-emitting units are connected in series through a charge generation layer (CGL). Under the action of an external electric field, the electrons and holes generated by the CGL are respectively injected into adjacent light-emitting units, and are recombined into excitons in the light-emitting units to emit light. Therefore, the material selection and design of the CGL are key factors affecting the optoelectronic performance and life of the stacked layer. The CGL layer is constructed in the form of a PN structure, in which the P-type material mainly generates holes, such as materials such as F4-TCNQ and HAT-CN, and the N-type doped material is doped with a low work function metal through the electron transport layer material, such as Alq3:Mg and Bphen:Li. Therefore, the performance of the electron transport material of the N-type doped material in the CGL has a very large impact on the device performance, and it is required to have efficient electron injection ability, transmission ability and high electron durability. At the same time, the heat resistance and film stability of the material are also important. Materials with low heat resistance are not only prone to decomposition when the material is evaporated, but also thermally decomposed by the heat generated by the device when the device is working, and cause material degradation. In the case of poor phase stability of the material film, the material also undergoes thin film crystallization in a short period of time, resulting in direct layer separation of the organic film layer and device degradation. Therefore, the materials used are required to have high heat resistance and good film stability. OLED has developed a variety of structures, among which a tandem OLED with multiple reflective layers stacked has been developed. The tandem OLED has the following structure: a stack of layers each formed by a hole injection layer (HIL) / hole transport layer (HTL) / light-emitting layer / electron transport layer (ETL) / electron injection layer (EIL) is stacked between the anode electrode and the cathode electrode. In particular, a charge generation layer (CGL) formed by NCGL (N-type charge generation layer) and PCGL (P-type charge generation layer) is arranged between the stack to generate charges or inject charges into the light-emitting layer.
[0004] However, in CGL, due to the energy level difference between NCGL and PCGL, the property of injecting electrons generated by charge generation at the interface between PCGL and the adjacent hole injection layer into NCGL is insufficient. In addition, when conventional NCGL is doped with alkali metal, the alkali metal diffuses into PCGL, resulting in a reduced OLED lifespan.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide an organic compound having a furan structure as a parent core and its application. The organic compound of the present invention can be used as a NCGL material, thereby reducing the driving voltage of OLED, improving the luminous efficiency of OLED, and extending the device life of OLED.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In one aspect, the present invention provides an organic compound whose parent core is a furan structure, wherein the organic compound has a structure shown in Formula 1:
[0009]
[0010] X1-X8 are the same as or different from each other, and are independently selected from N or CR, and at least one of them is a N atom, and the rest are CR;
[0011] R is selected from hydrogen, deuterium, substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N or S;
[0012] A and B are the same or different from each other and are independently selected from hydrogen, deuterium, phenyl, naphthyl, biphenyl, terphenyl or phenanthryl; A and B are connected to the cyclic group through a single bond or fused to the connected cyclic group;
[0013] L is selected from substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C 24 Heteroaryl, wherein the heteroatom is selected from O, N or S;
[0014] R1 is selected from hydrogen, deuterium, substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C 24 Heteroaryl, wherein the heteroatom is selected from O, N or S;
[0015] Ar is selected from substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C 24 Heteroaryl, wherein the heteroatom is selected from O, N or S;
[0016] In Formula 1, all hydrogen atoms are not substituted with deuterium, are partially substituted with deuterium, or are completely substituted with deuterium.
[0017] Preferably, when A and B are connected to the cyclic group via a single bond, the number of substitutions of A and B is mono-substitution, di-substitution, tri-substitution or tetra-substitution.
[0018] Preferably, when A and B are fused to the connected cyclic group, the fusion mode is that A is fused to the bond where X1 and X2 are located, or the bond where X2 and X3 are located, or the bond where X3 and X4 are located, and B is fused to the bond where X5 and X6 are located, or the bond where X6 and X7 are located, or the bond where X7 and X8 are located.
[0019] More preferably, L is selected from substituted or unsubstituted phenyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl or substituted or unsubstituted naphthyl.
[0020] Further preferably, R is selected from hydrogen, deuterium, phenyl, biphenyl, terphenyl or naphthyl.
[0021] Further preferably, R1 is selected from hydrogen, deuterium, phenyl, biphenyl, terphenyl, naphthyl or pyridyl.
[0022] Further preferably, Ar is selected from phenyl, biphenyl, terphenyl, naphthyl or pyridyl.
[0023] The above-mentioned "substitution" is mono- or poly-substitution. The above-mentioned substituted groups (for example, the substituted C6-C 24 Aryl, substituted C6-C 24 The substituent in the heteroaryl, substituted phenyl, substituted biphenyl, substituted terphenyl or substituted naphthyl) is selected from D, T, C1-C 10 Alkyl, C6-C 24 Aryl, C6-C 24 Heteroaryl, wherein the heteroatom is selected from O, N or S.
[0024] In the above technical solution, it is further preferred that the parent core is an organic compound containing a furan structure and is any one of the following structures, but not limited thereto:
[0025] ;
[0026] ;
[0027] ;
[0028] ;
[0029] ;
[0030] ;
[0031] ;
[0032] ;
[0033] ;
[0034] ;
[0035] ;
[0036] ;
[0037] ;
[0038] ;
[0039] ;
[0040] ;
[0041] ;
[0042] ;
[0043] ;
[0044] ;
[0045] ;
[0046] .
[0047] The preparation method of the organic compound of the present invention is as follows:
[0048]
[0049] Wherein Hal1 and Hal2 are selected from halogen.
[0050] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.0-1.1 eq) were put into a mixed solution of toluene, ethanol and water, followed by venting 3 times. Potassium carbonate (2.0 eq-2.5 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq-0.015 eq) were added under nitrogen protection, stirred evenly, heated to 90-100°C, and refluxed for 8-10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate. After the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 1.
[0051] Under nitrogen protection, the intermediate 1 (1.0 eq) and the raw material C (1.0-1.1 eq) were stirred evenly in a mixed solvent of 280 mL toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 0.05 eq-1.0 eq), palladium acetate (Pd(OAc)2) (0.05 eq-1.0 eq), and cesium carbonate (2.0 eq-2.5 eq) were added. After sufficient stirring, the temperature was raised to 90-100°C and stirred for reaction for 8-10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain the compound shown in the general formula 1.
[0052] In another aspect, the present invention provides an organic electroluminescent device, comprising an anode and a cathode and an organic thin film layer disposed between the anode and the cathode, wherein the organic thin film layer comprises the organic compound as described above.
[0053] Preferably, the organic thin film layer comprises a charge generation layer, and the material of the charge generation layer comprises the organic compound as described above.
[0054] Preferably, the charge generation layer includes an N-type charge generation layer and a P-type charge generation layer, and the material of the N-type charge generation layer includes the organic compound as described above.
[0055] Preferably, the organic thin film layer further comprises any one of a hole injection layer, a hole transport layer, an electron blocking layer, a light emitting layer, a hole blocking layer or an electron transport layer, or a combination of at least two thereof.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The compound provided by the present invention has a furan structure as a parent core structure, and the parent core contains unsaturated nitrogen atoms, so that the compound has suitable LUMO and HOMO energy levels, and the compound has efficient charge generation capability and efficient electron transmission performance, and can effectively improve the luminous efficiency of organic electroluminescent devices, while reducing the device driving voltage and extending the service life of organic electroluminescent devices. The compound of the present invention can effectively inhibit the film crystallinity of the molecule, improve the film stability and heat resistance durability of the material, and is conducive to improving the efficiency and life of the device.
[0058] When the compound of the present invention is used as an organic electroluminescent NCGL layer material in an OLED device, the device driving voltage can be effectively reduced, and the device luminous efficiency and lifespan can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of compound 2 prepared in Example 1. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0061] Example 1
[0062] Raw material C needs to be synthesized by the following preparation method
[0063]
[0064] Under nitrogen protection, raw materials C-1 (1.0 eq) and raw materials C-2 (1.0 eq) were put into DMF solution, K2CO3 (2.0 eq) was added under nitrogen protection, stirred evenly, heated to 150°C, and refluxed for 8 hours. After the reaction was completed, the temperature was cooled to room temperature, and the reaction solution was introduced into ice water to precipitate a solid to obtain the target product intermediate C-1.
[0065] Under nitrogen protection, the intermediate C-1 (1.0 eq) and the raw material C-3 (1.1 eq) were stirred evenly in a mixed solvent of 280 mL toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (0.05 eq), palladium acetate (Pd(OAc)2) (0.05 eq), and cesium carbonate (2.0 eq) were added. After sufficient stirring, the temperature was raised to 90°C and stirred for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain the raw material C (yield: 52.6%).
[0066]
[0067] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.0 eq) were put into a mixed solution of toluene, ethanol and water (volume ratio = 2:1:1), followed by ventilating 3 times, adding potassium carbonate (2.0 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) under nitrogen protection, stirring evenly, heating to 90°C, and reflux reaction for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 1.
[0068] Under nitrogen protection, intermediate 1 (1.0 eq) and raw material C (1.1 eq) were stirred evenly in 280 mL of a mixed solvent of toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (0.05 eq), palladium acetate (Pd(OAc)2) (0.05 eq), and cesium carbonate (2.0 eq) were added. After sufficient stirring, the temperature was raised to 90°C and stirred for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain compound 2 (yield: 70.2%).
[0069] The obtained compound 2 was tested and analyzed, and the results were as follows:
[0070] HPLC purity: >99.95%.
[0071] MS (ESI, m / Z): [M+H] + :551.19
[0072] Elemental Analysis:
[0073] Calculated values: C, 82.89; H, 4.03; N, 10.18; O, 2.91.
[0074] Test values are: C, 82.75; H, 4.42; N,10.34; O,3.18.
[0075] The H NMR spectrum of compound 2 is as follows Figure 1 shown.
[0076] Example 2
[0077] Raw material C needs to be synthesized by the following preparation method
[0078]
[0079] Under nitrogen protection, raw materials C-1 (1.0 eq) and raw materials C-2 (1.0 eq) were put into DMF solution, K2CO3 (2.0 eq) was added under nitrogen protection, stirred evenly, heated to 150°C, and refluxed for 8 hours. After the reaction was completed, the temperature was cooled to room temperature, and the reaction solution was introduced into ice water to precipitate a solid to obtain the target product intermediate C-1.
[0080] Under nitrogen protection, the intermediate C-1 (1.0 eq) and the raw material C-3 (1.1 eq) were stirred evenly in a mixed solvent of 280 mL toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (0.05 eq), palladium acetate (Pd(OAc)2) (0.05 eq), and cesium carbonate (2.0 eq) were added. After sufficient stirring, the temperature was raised to 90°C and stirred for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain the raw material C (yield: 53.1%).
[0081]
[0082] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.1 eq) were put into a mixed solution of toluene, ethanol and water (volume ratio = 2:1:1), followed by ventilating 3 times, adding potassium carbonate (2.0 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) under nitrogen protection, stirring evenly, heating to 90°C, and reflux reaction for 8 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain intermediate 1.
[0083] Under nitrogen protection, intermediate 1 (1.0 eq) and raw material C (1.1 eq) were stirred evenly in 280 mL of a mixed solvent of toluene, ethanol and water (volume ratio of 2:1:1), and X-Phos (0.05 eq), palladium acetate (Pd(OAc)2) (0.05 eq), and cesium carbonate (2.0 eq) were added. After sufficient stirring, the temperature was raised to 90°C and the reaction was stirred for 10 hours. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain the general compound 160 (yield: 68.2%).
[0084] The obtained compound 160 was tested and analyzed, and the results were as follows:
[0085] HPLC purity: >99.95%.
[0086] MS (ESI, m / Z): [M+H] + :577.21
[0087] Elemental Analysis:
[0088] Calculated values: C, 83.31; H, 4.20; N, 9.72; O, 2.77.
[0089] Test values: C, 83.12; H, 4.58; N, 10.09; O, 2.98.
[0090] The synthesis methods of other compounds are the same as those in the above embodiments and are not described in detail here.
[0091] Device application example 1: Preparation of organic electroluminescent devices
[0092] Anode: ITO anode: Wash the ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate with a coating thickness of 150nm in distilled water twice, ultrasonically wash for 30 minutes, and then repeatedly wash it with distilled water twice, ultrasonically wash for 10 minutes. After washing, bake it in a vacuum oven at 220℃ for 2 hours. After baking, cool it down and it can be used. Use this substrate as the anode, use an evaporation machine to carry out the evaporation device process, and evaporate other functional layers on it in sequence.
[0093] First hole injection layer: On the washed anode layer, HT-1 and P-1 with a thickness of 10 nm were evaporated by vacuum evaporation equipment, and the mass ratio of HT-1 to P-1 was 97:3 as the first hole injection layer;
[0094] First hole transport layer: On the first hole injection layer, HT-1 was then evaporated to a thickness of 24 nm as the first hole transport layer.
[0095] First electron blocking layer: EB-1 with a thickness of 5 nm was then evaporated on the first hole transport layer as the first electron blocking layer.
[0096] First light-emitting layer: After the evaporation of the first electron blocking material is completed, the light-emitting layer of the OLED light-emitting device is manufactured. The structure includes the OLED light-emitting layer using BH-1 as the main material and BD-1 as the doping material. The doping ratio of the doping material is 3% by weight, and the thickness of the light-emitting layer is 20nm.
[0097] First hole blocking layer: after the first light-emitting layer, 5 nm of HB-1 was evaporated as the first hole blocking layer;
[0098] First electron transport layer: After the first hole blocking layer, 10 nm of ETM-1 and Liq were vacuum evaporated, and the mass ratio of ETM-1:Liq was 1:1 as the first electron transport layer.
[0099] NCGL layer: On the first electron transport layer, an N-type charge generation layer (NCGL layer) was evaporated by a vacuum evaporation device, wherein the mass ratio of compound 2:Yb was 95:5 and the film thickness was 20 nm.
[0100] PCGL layer: On the NCGL layer, a co-evaporation layer of HT-1 and P-1 with a film thickness of 10 nm was evaporated using a vacuum evaporation device, and the mass ratio of HT-1 to P-1 was 95:5 as a P-CGL layer.
[0101] Second hole transport layer: HT-1 with a film thickness of 30 nm was then evaporated as the second hole transport layer.
[0102] Second electron blocking layer: EB-1 with a thickness of 5 nm was then evaporated on the second hole transport layer as the second electron blocking layer.
[0103] Second light-emitting layer: After the second electron blocking material is evaporated, the second light-emitting layer of the OLED light-emitting device is prepared. Its structure includes the OLED second light-emitting layer using BH-1 as the main material and BD-1 as the doping material. The doping ratio of the doping material is 3% by weight, and the light-emitting layer film thickness is 20nm.
[0104] Second hole blocking layer: After the second light-emitting layer, continue to vacuum evaporate 5nm of HB-1. This layer is the second hole blocking layer.
[0105] Second electron transport layer: On the second hole blocking layer, 15 nm of ETM-1 and Liq were evaporated, and the mass ratio of ETM-1:Liq was 1:1 as the second electron transport layer.
[0106] Second electron injection layer: On the second electron transport layer, YB with a film thickness of 1 nm was produced by vacuum evaporation equipment as the second electron injection layer.
[0107] Cathode: A 13nm Mg:Ag electrode layer was evaporated, with a mass ratio of Mg to Ag of 1:9. This layer is the cathode layer.
[0108] Light extraction layer: CPL-1 with a thickness of 65 nm is vacuum-deposited on the cathode as a light extraction layer;
[0109] The vapor-deposited substrate is packaged; first, the cleaned cover plate is coated with UV glue using a glue coating device, and then the coated cover plate is moved to the pressing section, and the vapor-deposited substrate is placed on the upper end of the cover plate, and finally the substrate and the cover plate are bonded by the bonding equipment, and the UV glue is cured by light.
[0110] The structural formula of the materials used is shown below:
[0111]
[0112] Device Application Example 2-Device Application Example 52 refers to the above method, and the compound 2 used in the device application example 1 is replaced by compound 160, compound 1, compound 4, compound 6, compound 8, compound 9, compound 12, compound 18, compound 20, compound 25, compound 31, compound 36, compound 42, compound 48, compound 51, compound 53, compound 56, compound 62, compound 66, compound 70, compound 79, compound 85, compound 93, compound 95, compound 105, compound 110, compound 118, compound 121, compound 125, compound 133, compound 137, compound 143, compound 148, compound 152, compound 157, compound 161, compound 167, compound 170, compound 175, compound 189, compound 192, compound 200, compound 212, compound 219, compound 223, compound 229, compound 232, compound 239, compound 241, compound 243, and compound 246 are used as compounds in the NCGL layer to prepare the corresponding organic electroluminescent devices.
[0113] Device control example: This control example provides an organic electroluminescent device. The only difference between the preparation method of the organic electroluminescent device and the device example 1 is that the organic electroluminescent device uses existing comparative compounds a, b, c, and d to replace the compound 2 in the NCGL layer in the device example 1 for evaporation to prepare the devices of device comparative examples 1-4. The chemical structural formulas of the comparative compounds a, b, c, and d are:
[0114]
[0115] The driving voltage, luminous efficiency and lifespan of the organic electroluminescent devices obtained from the device embodiments 2-52 and the device comparative examples 1-4 were characterized at a brightness of 1000 (nits). The test results are shown in Table 1 below.
[0116] Table 1
[0117]
[0118]
[0119] Note: In blue top-emitting devices, the current efficiency is greatly affected by chromaticity. Therefore, the influence of chromaticity on efficiency is taken into account, and the ratio of luminous efficiency to CIEy is defined as the BI value, that is, BI = (cd / A) / CIEy.
[0120] As can be seen from Table 1, in the laminated device, the compound provided by the present invention has a furan structure and a phenanthroline core structure, has efficient charge generation capability and efficient electron transport performance, can effectively improve the luminous efficiency of the organic electroluminescent device, while reducing the device driving voltage, and extending the service life of the organic electroluminescent device. When used as an NCGL material, compared with the comparative compound, the device voltage is reduced, and the device efficiency and device life are improved, further indicating that the compound of the present invention has good technical effects when used as an NCGL material in a laminated OLED device.
[0121] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate that the mother core of the present invention is an organic compound containing a furan structure and its application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A parent core is an organic compound containing a furan structure, characterized in that: The organic compound has a structure shown in Formula 1: ; X1-X8 are the same as or different from each other, and are independently selected from N or CR, and at least one of them is a N atom, and the rest are CR; R is selected from hydrogen, deuterium, substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C24 heteroaryl, wherein the heteroatom is selected from O, N or S; A and B are the same or different from each other and are independently selected from hydrogen, deuterium, phenyl, naphthyl, biphenyl, terphenyl or phenanthryl; A and B are connected to the cyclic group through a single bond or fused to the connected cyclic group; L is selected from substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C 24 Heteroaryl, wherein the heteroatom is selected from O, N or S; R1 is selected from hydrogen, deuterium, substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C 24 Heteroaryl, wherein the heteroatom is selected from O, N or S; Ar is selected from substituted or unsubstituted C6-C 24 Aryl, substituted or unsubstituted C6-C 24 Heteroaryl, wherein the heteroatom is selected from O, N or S; In Formula 1, all hydrogen atoms are not substituted with deuterium, are partially substituted with deuterium, or are completely substituted with deuterium.
2. The parent core according to claim 1 is an organic compound containing a furan structure, characterized in that: When A and B are connected to the cyclic group via a single bond, the number of substitutions of A and B is mono-, di-, tri- or tetra-substituted; When A and B are fused to the connected cyclic group, the fusion mode is that A is fused to the bond where X1 and X2 are located, or the bond where X2 and X3 are located, or the bond where X3 and X4 are located, and B is fused to the bond where X5 and X6 are located, or the bond where X6 and X7 are located, or the bond where X7 and X8 are located.
3. The mother core according to claim 1 is an organic compound containing a furan structure, characterized in that: L is selected from substituted or unsubstituted phenyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl or substituted or unsubstituted naphthyl.
4. The mother core according to claim 1 is an organic compound containing a furan structure, characterized in that: R is selected from hydrogen, deuterium, phenyl, biphenyl, terphenyl or naphthyl.
5. The mother core according to claim 1 is an organic compound containing a furan structure, characterized in that: R1 is selected from hydrogen, deuterium, phenyl, biphenyl, terphenyl, naphthyl or pyridyl.
6. The mother core according to claim 1 is an organic compound containing a furan structure, characterized in that: Ar is selected from phenyl, biphenyl, terphenyl, naphthyl or pyridyl.
7. The mother core according to claim 1 is an organic compound containing a furan structure, characterized in that: The substituents in the substituted C6-C24 aryl and substituted C6-C24 heteroaryl are selected from D, T, C1-C10 alkyl, C6-C24 aryl, C6-C24 heteroaryl, wherein the heteroatom is selected from O, N or S.
8. The mother core according to claim 1 is an organic compound containing a furan structure, characterized in that: The organic compound is any one of the following compounds: ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; ; 。 9. An organic electroluminescent device, characterized in that: The organic electroluminescent device comprises an anode and a cathode and an organic thin film layer arranged between the anode and the cathode, wherein the organic thin film layer comprises the organic compound whose parent core is a furan structure as claimed in any one of claims 1 to 8.
10. The organic electroluminescent device according to claim 9, characterized in that: The organic thin film layer comprises a charge generation layer, the charge generation layer comprises an N-type charge generation layer and a P-type charge generation layer, and the material of the N-type charge generation layer comprises an organic compound whose parent core is a furan structure as described in any one of claims 1 to 8; The organic thin film layer further comprises any one of a hole injection layer, a hole transport layer, an electron blocking layer, a light emitting layer, a hole blocking layer or an electron transport layer, or a combination of at least two thereof.
Citation Information
Patent Citations
Heterocyclic compound and organic light emitting device comprising the same
CN110128433A
Heterocyclic compound and organic light-emitting device comprising same
CN111247648A
Furochrysene derivative, application thereof and OLED device containing chrysene derivative
CN111777580A
Heterocyclic compound and organic light emitting device comprising same
CN113056470A
Organic compound containing dianthracene structure and application of organic compound in organic electroluminescent device
CN114315775A